Epidermal growth factor receptor tyrosine kinase inhibitors as first-line treatment for postoperative recurrent EGFR-mutated lung adenocarcinoma: a multi-institutional retrospective study. (23rd August 2022) - Miyata, Ryo; Hamaji, Masatsugu; Kawaguchi, Atsushi; Shimazu, Yumeta; Ikeda, Masaki; Ishikawa, Masashi; Kayawake, Hidenao; Menju, Toshi; Kobayashi, Masashi; Okumura, Norihito; Sakaguchi, Yasuto; Sonobe, Makoto; et al.
Abstract: OBJECTIVES: The aim of this study was to analyse the long-term survival outcomes and prognostic factors of patients receiving epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) as first-line treatment for postoperative recurrent EGFR -mutated lung adenocarcinoma. METHODS: Using a multi-institutional database, we performed a retrospective chart review to identify all patients who had undergone complete resection of stage I–III EGFR -mutated lung adenocarcinoma at 11 acute care hospitals between 2009 and 2016 and had received first-line EGFR-TKI treatment for postoperative recurrence. Adverse events, progression-free survival (PFS) and overall survival (OS) were investigated. Survival outcomes were assessed using Kaplan–Meier analysis. Cox proportional hazards models were used to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs) for PFS and OS. RESULTS: The study sample comprised 154 patients with a median age of 69. The total numbers of events were 101 for PFS and 60 for OS. The median PFS and OS were 26.1 and 55.4 months, respectively. In the multivariable analysis, EGFR ex 21 L858R mutation (HR: 1.71, 95% CI: 1.15–2.55) and shorter disease-free intervals (HR: 0.98, 95% CI: 0.96–0.99) were significantly associated with shorter PFS. Age (HR: 1.03, 95% CI: 1.00–1.07), smoking history (HR: 2.31, 95% CI: 1.35–3.94) and pathological N2 disease at the initial surgery (HR: 2.30, 95% CI: 1.32–4.00) were significantly associated with shorter OS. CONCLUSIONS: First-line EGFR-TKI treatment was generally associated with favourable survival outcomes in patients with postoperative recurrent EGFR -mutated lung adenocarcinoma. EGFR ex 21 L858R mutation may be an important prognostic factor for shorter PFS. Abstract : Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) have improved long-term survival outcomes in patients with EGFR mutation-positive stage IV non-small-cell lung cancer (NSCLC) [1–3].